The Returns to Language Skills in the US Labor Market - Ingo Isphording; Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
This paper uses data from the 2010 American Community Survey (ACS) to study the returns to language skills of child and adult migrants in the US labor market. We employ an instrumental variable strategy, which exploits differences in language acquisition profiles between immigrants from English- and non-English-speaking countries of origin, to address problems related to endogeneity and measurement error. We find significantly positive returns to language skills and demonstrate that education is an important channel through which language skills affect wages of child migrants. Although the returns of adult migrants do not depend on education, we find that child and adult migrants exhibit similar returns to language skills. – – Dieses Papier verwendet Daten des American Community Survey (ACS), um die Renditen von Sprachfähigkeiten von Einwanderern, die entweder als Kinder oder als Erwachsene in die USA eingewandert sind, zu schätzen. Wir verwenden Instrumentenvariablen, welche Unterschiede in Spracherwerbsprofilen zwischen Einwanderern aus Englisch- und Nicht-Englischsprachigen Herkunftsländern ausnutzen, um Endogenitäts- und Messfehlerprobleme zu adressieren. Wir finden positive Renditen von Sprachfähigkeiten und zeigen, dass Bildung ein wichtiger Kanal ist, durch welchen Sprachfähigkeiten die Löhne von Einwanderern, die als Kinder in die USA gekommen sind, beeinflussen. Obwohl die Renditen von Einwanderern, die als Erwachsene in die USA gekommen sind, nicht von Bildung abhängen, finden wir ähnliche Renditen für beide Einwanderungsgruppen.
Keywords: F22; J24; J31; 330; international migration; language skills; labor productivity